2017
DOI: 10.3389/fpls.2017.01468
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Assembly and Systematic Identification of Novel Cytochrome P450s in Taxus chinensis

Abstract: Taxus spp. is a highly valuable medicinal plant with multiple pharmacological effects on various cancers. Cytochrome P450s (CYP450s) play important roles in the biosynthesis of active compounds in Taxus spp., such as the famous diterpenoid, Taxol. However, some specific CYP450 enzymes involved in the biosynthesis of Taxol remain unknown, and the systematic identification of CYP450s in Taxus has not been reported. In this study, 118 full-length and 175 partial CYP450 genes were identified in Taxus chinensis tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 46 publications
5
34
0
Order By: Relevance
“…And with more and more genome sequences available, an ever-growing number of CYP450 sequences were identified. To date, the genes have been identified in many plant species at a whole-genome scale, such as Arabidopsis [30], Oryza sativa [31], Nelumbo nucifera [32], Glycine max [33] and Taxus chinensis [34], whereas no systematical investigation of CYP450s has been performed in wheat and maize. In the present study, we carried out the first comprehensive analysis of wheat and maize genomes for CYP450 superfamily.…”
Section: Introductionmentioning
confidence: 99%
“…And with more and more genome sequences available, an ever-growing number of CYP450 sequences were identified. To date, the genes have been identified in many plant species at a whole-genome scale, such as Arabidopsis [30], Oryza sativa [31], Nelumbo nucifera [32], Glycine max [33] and Taxus chinensis [34], whereas no systematical investigation of CYP450s has been performed in wheat and maize. In the present study, we carried out the first comprehensive analysis of wheat and maize genomes for CYP450 superfamily.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of next-generation sequencing technologies such as RNA-Seq has allowed for the more rapid and cost-effective identification of CYP450s [6]. More recent transcriptomic studies have, for example, detected 116 full-length and 135 partial-length CYP450s in Salvia miltiorrhiza [7], with similar work being performed in Lonicera japonica [8] and Taxus chinensis [9]. More recently, a genome-wide study of rice identified 355 CYP450s that clustered into 10 clans including 45 families [10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, transcriptome assay with next-generation sequencing has been extensively used to explore the novel genes underlying active-ingredient biosynthesis pathways in medicinal plants. Some include the excavation of genes encoding enzymes that catalyze distinct steps related to the biosynthetic pathway of ginsenosides in Panax ginseng [13], triterpenoid saponin biosynthesis in Bacopa monnieri [14], artemisinin in Artemisia annua [15,16], avonoid biosynthesis in sa ower [17], glycyrrhizin in Glycyrrhiza uralensis [18], rubber in Parthenium argentatum [19], cardiac glycoside in Calotropis procera [20], terpenoid in Cinnamomum camphora [21], cannabinoids in Cannabis sativa [22], withanolide in Withania somnifera [23], picrosides in Picrorhiza kurrooa [24], paclitaxel in Taxus chinensis [25] and steroidal saponins in Asparagus racemosus [26].…”
Section: Introductionmentioning
confidence: 99%